2023
DOI: 10.1101/2023.02.25.23286432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

International Multi-Specialty Expert Physician Preoperative Identification of Extranodal Extension in Oropharyngeal Cancer Patients using Computed Tomography: Prospective Blinded Human Inter-Observer Performance Evaluation

Abstract: Background: Extranodal extension (ENE) is an important adverse prognostic factor in oropharyngeal cancer (OPC) and is often employed in therapeutic decision making. Clinician-based determination of ENE from radiological imaging is a difficult task with high inter-observer variability. However, the role of clinical specialty on the determination of ENE has been unexplored. Methods: Pre-therapy computed tomography (CT) images for 24 human papillomavirus-positive (HPV+) OPC patients were selected for the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…67 The presence of extranodal extension (ENE) in neck nodes portends more aggressive cancer, though it is very challenging to detect on imaging. 68 Kann et al developed and validated a deep CNN model to predict pathologic ENE on CT imaging 69 and used ECOG-ACRIN E3311 data in a quality improvement study to suggest better ability to predict pathologic ENE compared with head and neck radiologists. 70 Genomics-driven precision oncology Several categories of precision oncology using clinicogenomic data are emerging, ranging from improving prognostication to biomarker selection to drug development.…”
Section: Radiation Oncologymentioning
confidence: 99%
“…67 The presence of extranodal extension (ENE) in neck nodes portends more aggressive cancer, though it is very challenging to detect on imaging. 68 Kann et al developed and validated a deep CNN model to predict pathologic ENE on CT imaging 69 and used ECOG-ACRIN E3311 data in a quality improvement study to suggest better ability to predict pathologic ENE compared with head and neck radiologists. 70 Genomics-driven precision oncology Several categories of precision oncology using clinicogenomic data are emerging, ranging from improving prognostication to biomarker selection to drug development.…”
Section: Radiation Oncologymentioning
confidence: 99%
“…A multispecialty expert physicians’ group [74 ▪ ] in an observation performance evaluation study was asked to identify the presence of rENE+ in CT of HPV and OPSCC patients. The median accuracy of rENE and discrimination was 0.57 with significant differences between radiologists and surgeons for Brier score (0.33 vs. 0.26), radiation oncologists/surgeons for sensitivity (0.48 vs. 0.69), and radiation oncologists and radiologists/surgeons for specificity (0.89 vs. 0.56).…”
Section: Staging Of Extranodal Extension By Imaging (Radiological Ext...mentioning
confidence: 99%
“…Contrast-enhanced computed tomography (CT) scan is the most widely used method to predict ENE status for HNSCC patients in clinical practice. However, the literature revealed that this method has limited diagnostic performance, with reported sensitivity ranging from 43.7 to 69% and the area under the receiver operating characteristic curve (AUC) ranging from 0.6 to 0.69 [ 9 13 ]. Furthermore, high inter-observer variability is also reported [ 9 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%